Maternal and infant affect at 4 months predicts performance and verbal IQ at 4 and 7 years in a diverse population. Issue 5 (23rd October 2016) - Sheinkopf, Stephen J.; Tenenbaum, Elena J.; Messinger, Daniel S.; Miller‐Loncar, Cynthia L.; Tronick, Ed; Lagasse, Linda L.; Shankaran, Seetha; Bada, Henrietta; Bauer, Charles; Whitaker, Toni; Hammond, Jane; Lester, Barry M.
Abstract: Using existing longitudinal data from 570 infants in the Maternal Lifestyle Study, we explored the predictive value of maternal and infant affect and maternal vocalizations during 2 minutes of face‐to‐face interactions at 4 months on IQ scores at 4.5 and 7 years. After controlling for demographic factors, maternal depression, and prenatal drug exposure, maternal positive affect and maternal positive vocalizations emerged as predictors of both verbal and performance IQ at 4.5 and 7 years. Although infant positive affect during the interaction with the mother was not predictive of these outcome measures, infant positive affect towards an examiner predicted verbal but not performance IQ at 4.5 years. These results suggest that maternal positive affect may index emotional engagement in interaction that facilitates both verbal and nonverbal cognitive development, while infant social positive affect is specifically related to the acquisition of verbal reasoning abilities. These findings are significant because they are based on a discrete snapshot of observable behavior in infancy (just 2 minutes of interaction), because they extend the range of maternal behaviors and characteristics known to support positive developmental outcomes, and because they are derived from high‐risk infants where prevention efforts may be beneficial. Potential mechanisms for these associations are discussed, as are the clinical implications for identifying dyads most in need of targeted interventions. Abstract : Maternal positive affect directed towards infants at 4 months of age was positively related to later verbal and nonverbal IQ, and displays of positive affect by the infant correlated with later verbal IQ. Early positive affective displays by mothers during dyadic interactions may index emotional engagement in interaction that facilitates both verbal and nonverbal cognitive development, while infant social positive affect may be specifically related to the acquisition of verbal reasoning abilities.